The Correlation Between the Use of Realia Media and Students’ Vocabulary Mastery - Jessi Juniarti; Henni Rosa Triwardani; Rinaepi, Rinaepi (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2024)
Realia media is a real object that  used in teaching learning to help the teaching process to be more effective. this media involves almost all five senses from seeing, touching, hearing, observing directly and providing real experience to students. real media here is classified into three kind there are: real objects, artificial objects, and modified artificial objects (similar to real objects). The use of this media can help the process of introducing new vocabulary to be easily remembered and can explore more vocabulary even though only from one object. The aim of this study is to find out how is the significant correlation between the use of Realia media and student vocabulary mastery at seventh grade SMPIT Umuul Qurro Tasikmalaya. This research is quantitative research with a correlational quantitative research design. The research sample was 35 students from 72 students who became the population. In taking sample the researcher used the Simple Random Sampling technique. Data collection techniques by distributing questionnaires related to the use of Realia media and vocabulary tests to find out how far the mastery of student vocabulary. The data analysis technique used is descriptive and inferential using the product moment correlation formula. Based on the results of data processing and analysis using the spss 25 program, the results of the correlation between the use of Realia media and student vocabulary mastery  0.677. this result is at the "strong" level because the value of 0.677 is in the Coefficient Interval 0.60-0.799 with a significance value of 0.000 less than 0.05 or 5%.  it is concluded that H0  is rejected, and Ha is accepted. Means, there is a significant correlation between the use of Realia media and student vocabulary mastery at seventh grade SMPIT Umuul Qurro Tasikmalaya.